Association of systemic inflammatory response index and stroke: a cross-sectional study of NHANES, 2005–2018 - Tian, Aokai; Zheng, Yafang; Jin, Jing; Huang, Chunyuan (Frontiers in Neurology, 2025)
BackgroundMany inflammatory markers like systemic immune-inflammatory index (SII), neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) are associated with stroke. However, studies on the relationship between stroke and systemic inflammatory response index (SIRI) are scarce. This study was aimed at evaluating the potential association of SIRI with stroke.MethodsOur cross-sectional study included adults with sufficient SIRI and stroke data from the 2005-2018 National Health and Nutrition Examination Survey (NHANES). We used multivariable logistic regression, interaction tests, smoothed curve fitting, and subgroup analysis for assessing the independent relationship between SIRI and stroke.ResultsOf 36,176 participants in this study, 1,414 (3.9%) had experienced a stroke. In a fully adjusted model, the systemic inflammatory response index displayed a significant and positive correlation with stroke (odds ratio [OR] = 1.09, 95% confidence interval [CI] = 1.04–1.15, p = 0.0006). Meanwhile, the odds of stroke increased by 39% in the 4th quartile, relative to the 1st quartile (OR = 1.39, 95% CI = 1.17–1.65, p = 0.0002). Additional interaction tests and subgroup analysis revealed that age, sex, race, education, marriage, BMI (body mass index), smoking, diabetes mellitus, hypertension, and coronary heart disease (CHD) were not positively correlated (p interaction >0.05). Moreover, we also found a nonlinear correlation between SIRI and stroke, with an inflection point of 2.17.ConclusionOur results indicate that SIRI is significantly and positively related to stroke; however, its role in stroke needs to be further confirmed by large-scale prospective studies.